Predictive Validity of Peer Assessment in Micro-Teaching: Correlation with Teacher Ratings among Indonesian Preservice EFL Teachers - Santi Farmasari; Lalu Ali Wardana; La Ode Alfin Haris Munandar; Hartati Suryaningsih (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study investigates the predictive validity of peer assessment of teacher evaluations in English micro-teaching performance among preservice teachers Methodology: This study used a quantitative correlational-predictive design with 48 preservice teachers selected through random cluster sampling. The study used peer and teacher performance assessment rubrics covering eight teaching skills, which were previously validated by two experts (CVI = 1.0). Data were analyzed using Pearson correlation, linear regression, and paired-sample t-tests to examine predictive validity, alignment, and discrepancies between peer and teacher evaluations in micro-teaching performance. Main Findings: Data reveal a moderate to strong correlation between peer and teacher scores (r = 0.645, p < 0.001), with peer assessments significantly predicting teacher evaluations (R² = 0.416). However, peer scores were consistently lower (M = 34.02 vs. 38.33, p < 0.001), particularly in complex areas like classroom management and reinforcement. This highlights peer assessment’s value as a supplementary tool for evaluating teaching and fostering reflection, while underscoring the need for assessor training and rubric calibration to ensure reliability. Novelty/Originality of this study: This study brings a new perspective by exploring whether peer assessment in English micro-teaching can actually predict teacher evaluations. Unlike most research that sees peer review only as a learning aid, this study shows peers can meaningfully mirror teacher judgments, while also revealing where their views differ. The findings highlight the potential of peer assessment as both a learning and an evaluative tool in teacher education.